Anthraquinone-based MOF photocatalytic material as well as preparation method and application thereof
The anthraquinone-based MOF photocatalytic material is prepared in solvent thermal reaction and is used to photocatalyze benzylamine self-coupling reaction, which solves the poor selectivity and environmental protection of imine synthesis, and achieves high-efficiency and environmentally friendly imine synthesis, and has good catalysts cyclic stability.
Patent Information
- Application Number
- CN202411173738.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-26
AI Technical Summary
In the prior art, the synthesis method of imine has poor selectivity, complex by-product treatment, and is not environmentally friendly, and lacks high catalytic activity and recyclable non-precious metal heterophasic catalysts.
Anthraquinone-based MOF photocatalytic material is prepared by 2,6-bis(pyrazole-4-yl)-9,10 anthraquinone and nickel source in a mixed solvent by solvothermal reaction, and is used to photocatalyze benzylamine autocoupling A combination reaction is performed to prepare imine compounds.
High selectivity and high yield imine synthesis is achieved, the catalytic reaction efficiency is high, and the catalyst can be recycled, and the product yield is still 92% after 5 cycles.
Smart Images

Figure CN119259114A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to an anthraquinone-based MOF photocatalytic material and a preparation method and application thereof. Background Art
[0002] As intermediates and active building blocks for drug synthesis, imines are often used in the preparation of drug molecules. Imines are usually prepared by a condensation reaction between amines and carbonyl compounds, which usually requires unstable aldehydes as raw materials, Lewis acid catalysts and dehydrating agents. However, the reaction has poor selectivity and functional group tolerance, and its post-processing and purification process is complicated, requiring the removal of by-products, dehydrating agents and catalyst residues. Considering the wide range of uses of imines as biologically active substances, the selective aerobic oxidation of amines to prepare imines is a key reaction for laboratory and commercial applications. Therefore, it is necessary to develop a mild, green and sustainable method for the synthesis of imines.
[0003] In recent years, visible light-induced transition metal catalysis not only eliminates the trouble of precious metal complexes, but also does not require the use of additional photosensitizers. The combination of catalyst and substrate occurs synergistically with the light-induced single electron transfer (SET) process, which reduces the temperature at which the redox process occurs, thereby activating organic molecules with high redox potentials, which is sometimes unattainable with typical photoredox catalysts. From the concept of green and sustainable development, it is crucial to develop non-precious metal heterogeneous catalysts with high catalytic activity, green, and recyclable.
[0004] Metal-organic frameworks (MOFs) are a class of porous crystalline materials self-assembled from metal ions / clusters and organic linkers. MOFs have become important materials for energy and environment-related applications, especially in heterogeneous photocatalysis, due to their high porosity, high adsorption, large specific surface area and abundant active sites. Visible light-driven photoredox conversions are often used to prepare high-value-added organic compounds due to their unique advantages such as mild conditions and green sustainability. Molecular oxygen (O2) has attracted increasing attention in organic synthesis as an economical and abundant oxidant. For example, photocatalysts that can absorb visible light and generate electron-hole pairs can convert O2 into reactive oxygen species (ROS) through single electron transfer (SET) and energy transfer (ET) processes, and the obtained ROS further interact with substrate molecules for oxidative transformation.
[0005] Organic photosensitizers can be integrated into the MOF framework as building blocks. For example, the anthraquinone unit is well-known for its photon absorption efficiency. Anthraquinone compounds are the most numerous class of compounds among various natural quinone compounds. They are important dyes and pharmaceutical intermediates, and substances with good optical activity. Due to their high photosensitivity, high triplet energy and relatively long triplet lifetime, they are widely used as organic photocatalysts to participate in organic photocatalytic reactions. Their electron-withdrawing properties make these substances have the potential to transfer electrons in the reaction, so anthraquinone compounds can be used as active ligands in the field of photocatalysis. For example, the invention patent with publication number CN116371471A discloses a method consisting of a photosensitizing ligand The photosensitive MOF catalyst material with large hexagonal channels obtained by self-assembly with transition metal nitrate has high catalytic activity when used for photocatalytic reduction of CO2. Another example is the invention patent with publication number CN117700766A, which discloses an anthraquinone-based two-dimensional MOF photocatalyst and its preparation method and application. The photocatalyst is synthesized by using 2,6-di((E)-2-(pyridine-4-yl)vinyl)anthracene-9,10-dione as a functional ligand and auxiliary carboxylic acid and metal Zn(II) ion coordination, wherein the auxiliary carboxylic acid is 5-methylisophthalic acid, isophthalic acid or 5-fluoroisophthalic acid. The MOF photocatalyst described in the invention has high selectivity and high yield for the self-coupling reaction of photocatalytic benzylamine and its derivatives, wherein the reaction selectivity reaches 100%, the product yield can reach 98.24%, the catalytic reaction efficiency is high, and it can be recycled many times. However, there are currently no reports on the use of anthraquinone photosensitizing ligands to construct Ni8-MOF materials and their use in photocatalytic benzylamine self-coupling reactions to prepare imine compounds. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an anthraquinone-based MOF photocatalytic material with high catalytic reaction efficiency and a preparation method and application thereof.
[0007] The first object of the present invention is to provide an anthraquinone-based MOF photocatalytic material, which is obtained by a solvothermal reaction of a ligand DPAq and a nickel source in a mixed solvent; wherein the ligand DPAq is 2,6-bis(pyrazol-4-yl)-9,10-anthraquinone, and the mixed solvent is a composition of N,N-dimethylformamide and water.
[0008] The anthraquinone-based MOF photocatalytic material is in the form of a yellow-brown powder. The nickel source involved in the above scheme is Ni(OAc)2·4H2O; in the composition of the mixed solvent, the volume ratio of N,N-dimethylformamide and water is preferably 1 to 10:1, and more preferably 3 to 5:1. The ligand DPAq and the nickel source can be directly dissolved in the mixed solvent and then subjected to a solvothermal reaction, or the ligand DPAq and the nickel source can be dissolved in N,N-dimethylformamide and water respectively, and the two solutions are mixed and then subjected to a solvothermal reaction. Regardless of the method used, the ratio of the amount of nickel source to the amount of water in the mixed solvent is preferably 7 to 10 mg: 1 mL, and the ratio of the amount of ligand DPAq to the amount of N,N-dimethylformamide in the mixed solvent is preferably 1 to 3 mg: 1 mL. The solvent thermal reaction is usually carried out at ≥100°C, more preferably at 140-160°C; when the reaction is carried out at 140-160°C, the reaction time is preferably controlled at 10-12h.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned anthraquinone-based MOF photocatalytic material, comprising: taking a ligand DPAq and a nickel source and dissolving them in N,N-dimethylformamide and water respectively, mixing the two solutions and then subjecting them to a solvothermal reaction to obtain the photocatalytic material.
[0010] In the preparation method of the anthraquinone-based MOF photocatalytic material, the selection of the nickel source, the solvent thermal reaction parameters, etc. are all as described above. In the preparation method, N,N-dimethylformamide and water constitute the aforementioned mixed solvent, and the ratio of N,N-dimethylformamide and water, and the relationship between them and the amount of DPAq and the nickel source are the same as described above. The ratio of the ligand DPAq and the nickel source is a stoichiometric ratio. In a specific embodiment, the molar ratio of the ligand DPAq and the nickel source is 3:4.
[0011] The third object of the present invention is to provide an anthraquinone-based MOF photocatalytic material crystal, which is octahedral and belongs to the cubic crystal system. Space group, unit cell parameters are: α=90.00°, β=90.00°, γ=90.00°. The nickel ion in the metal center of the anthraquinone-based MOF photocatalytic material crystal is positive divalent, and the MOF framework consists of an inorganic secondary building unit (SBU) and a Ni8 cluster, which are connected to 12 DPAq connectors to generate a three-dimensional porous framework with octahedral and tetrahedral cavities.
[0012] The fourth object of the present invention is to provide a method for preparing the above-mentioned anthraquinone-based MOF photocatalytic material crystals, comprising: taking a ligand DPAq and a nickel source and placing them in a mixed solvent, adjusting the pH of the system to acidic, reacting under heating conditions, cooling the reaction solution, and precipitating crystals to obtain the obtained product; wherein the ligand DPAq is 2,6-bis(pyrazole-4-yl)-9,10-anthraquinone, and the mixed solvent is a combination of N,N-dimethylformamide and water.
[0013] In the preparation method of the above-mentioned anthraquinone-based MOF photocatalytic material crystal, the pH of the system is adjusted to acidic using an organic acid or an inorganic acid, such as nitric acid, hydrochloric acid or sulfuric acid, and preferably dilute nitric acid (such as 0.2-0.3 mol / L) is used for adjustment. Preferably, the pH of the system is adjusted to 4.0-6.5, and more preferably, the pH of the system is adjusted to 4.0-5.0. In the preparation method of the crystal, the heating reaction is preferably carried out at ≥100°C, more preferably at 110-130°C; when the reaction is carried out at 110-130°C, the reaction time is preferably controlled at 60-96h. The selection of the nickel source and the ratio of the mixed solvent involved in the preparation method are the same as those described above.
[0014] A fifth object of the present invention is to provide an application of anthraquinone-based MOF photocatalytic material or anthraquinone-based MOF photocatalytic material crystals in the photocatalytic self-coupling reaction of benzylamine to prepare imine compounds.
[0015] In the present application, the structure of the ligand DPAq is shown in the following formula (1):
[0016]
[0017] The ligand DPAq can be prepared with reference to the existing literature (Wu K, Liu XY, Cheng PW, et al. Linker Engineering for Reactive Oxygen Species Generation Efficiency in Ultra-Stable Nickel-Based Metal–Organic Frameworks[J]. Journal of the American Chemical Society, 2023, 145(34): 18931-8.). Specifically, the preparation is carried out by the following method: 2,6-dibromoanthraquinone and 1-THP-4-pyrazole boronic acid pinacol ester (1-(2-Tetrahydropyranyl)-1H-pyrazole-4-boronicacid pinacol ester) are placed in a composition of an organic solvent and water, a catalyst is added, the system is adjusted to be weakly alkaline, and a heating reaction is carried out under the protection of an inert atmosphere (such as nitrogen, helium, etc.), the reaction material is filtered, and the filter cake is subjected to silica gel column chromatography to obtain an intermediate product, and the tetrahydropyran protective group of the intermediate product is deprotected to obtain the ligand DPAq.
[0018] In the above method for preparing the ligand DPAq, the organic solvent is preferably N,N-dimethylformamide, N,N-dimethylacetamide, 1,4-dioxane or acetonitrile, and the volume ratio of the organic solvent to water is preferably 3 to 5:1. The catalyst is preferably tetrakis(triphenylphosphine)palladium. The system is adjusted to weak alkalinity by alkaline substances (such as potassium carbonate, sodium carbonate, sodium bicarbonate or triethylamine, etc.), preferably the pH of the system is adjusted to 8.0 to 9.0. The heating reaction is preferably carried out at 100 to 120°C, and the reaction time is usually controlled at 48 to 72h. When purifying by silica gel column chromatography, the developing agent used is a combination of petroleum ether and ethyl acetate, preferably the volume ratio of petroleum ether to ethyl acetate is 1:1. The tetrahydropyran protective group of the obtained intermediate product is deprotected by conventional methods, such as placing the obtained intermediate product in ethanol, and removing the tetrahydropyran protective group of the obtained intermediate product under acidic conditions, and the removal is usually heated to 60 to 80°C in an air environment and stirred for 8 to 12h. In the method, the mass ratio of 2,6-dibromoanthraquinone to 1-THP-4-pyrazoleboric acid pinacol ester is usually 1:2-3, the mass ratio of 1-THP-4-pyrazoleboric acid pinacol ester to the organic solvent is preferably 1 g:15-25 mL, and the amount of the catalyst used is preferably 0.15-0.25 times the mass of 1-THP-4-pyrazoleboric acid pinacol ester.
[0019] Compared with the prior art, the present invention coordinates Ni8 clusters and 2,6-bis(pyrazol-4-yl)-9,10-anthraquinone to obtain anthraquinone-based MOF photocatalytic materials and their crystals. The applicant's experimental results show that the anthraquinone-based MOF photocatalytic material exhibits a suitable band gap and good ROS generation efficiency. When applied to the benzylamine coupling reaction, it exhibits excellent catalytic activity and selectivity, wherein the reaction selectivity reaches 100%, the product yield can reach 97%, and the catalytic reaction efficiency is high; and it can be recycled, and the product yield can still reach 92% after being recycled 5 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The ligand prepared in Example 1 1 H and 13 C NMR spectrum, where (a) is 1 H NMR spectrum, (b) 13 C NMR spectrum.
[0021] Figure 2 is the ligand H2pbp prepared in Comparative Example 1 1 H and 13 C NMR spectrum, where (a) is 1 H NMR spectrum, (b) 13 C NMR spectrum.
[0022] Figure 3 The ligand prepared in Comparative Example 2 1 H and 13 C NMR spectrum, where (a) is 1 H NMR spectrum, (b) 13 C NMR spectrum.
[0023] Figure 4 These are infrared spectra of the ligands and MOF photocatalytic materials, GXMZU105 and GXMZU106 prepared in Example 1, Comparative Examples 1 and 2, wherein (a) is the infrared spectrum of the ligand H2pbp and MOF photocatalytic material GXMZU104 prepared in Comparative Example 1, (b) is the infrared spectrum of the ligand DPA and MOF photocatalytic material GXMZU105 prepared in Comparative Example 2, and (c) is the infrared spectrum of the ligand DPAq and MOF photocatalytic material GXMZU106 prepared in Example 1.
[0024] Figure 5 These are the XRD diagrams of GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1 and 2, respectively.
[0025] Figure 6Solid UV-visible diffuse reflectance images of GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1, Comparative Examples 1 and 2, respectively.
[0026] Figure 7 These are the EIS graphs of GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1 and 2, respectively.
[0027] Figure 8 The photocurrent response curves of GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1 and 2 respectively.
[0028] Fig. 9 The XPS spectra of GXMZU106 prepared in Example 1 before and after the photocatalytic benzylamine self-coupling reaction cycle.
[0029] Fig.10 This is a crystal structure diagram of the anthraquinone-based MOF photocatalytic material crystal prepared in Example 2.
[0030] Fig.11 These are the SEM and EDS images of the anthraquinone-based MOF photocatalytic material crystals prepared in Example 2.
[0031] Fig.12 This is a graph showing the yield and selectivity results of five cycles of the photocatalytic benzylamine self-coupling reaction using GXMZU106 in Example 1. DETAILED DESCRIPTION
[0032] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0033] Example 1: Preparation of anthraquinone-based MOF photocatalytic materials
[0034] (1) Preparation of functional ligands:
[0035]
[0036] 1g of 2,6-dibromoanthraquinone and 2.7184g of 1-THP-4-pyrazoleboronic acid pinacol ester were placed in N,N-dimethylformamide (45mL) and water (16mL), and 1.052g of anhydrous K2CO3 and 0.4396g of Pd(PPh3)4 were added, and the mixture was heated to 110°C and stirred for 48h under a nitrogen atmosphere. After the reaction was completed, the reaction mixture was cooled to room temperature, 50mL of saturated sodium chloride aqueous solution was added to completely precipitate the solid, and then filtered to obtain a yellow solid, which was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1, volume ratio) to obtain an intermediate product. The tetrahydropyran protecting group of the intermediate product was deprotected by placing the intermediate product in 50 mL of ethanol, adding 25 mL of hydrochloric acid (1.0 mol / L), heating to 80° C. and stirring for 10 h, cooling at room temperature, filtering, washing the precipitate with ethanol and adding it to a beaker containing 100 mL of distilled water, adjusting the pH to 5.0-7.0 (specifically to pH=7.0 in this example) with sodium hydroxide (aq, 0.5 mol / L), filtering, washing the filter cake with distilled water until neutral, and then rinsing with a small amount of ethanol and ether to obtain a bright yellow solid (referred to as ligand DPAq) with a yield of 88%.
[0037] (2) Preparation of anthraquinone-based MOF photocatalytic material: 33 mg of ligand DPAq was dissolved in 16 mL of N,N-dimethylformamide, and 31.8 mg of Ni(OAc)2·4H2O was dissolved in 4 mL of water. The two solutions were then mixed and heated to 150°C in a reactor for a solvothermal reaction until completion (about 9 h). After the reaction was completed, the solution was cooled to room temperature and solid precipitated. The solid was collected and washed with solvent N,N-dimethylformamide, ethanol and ether, and dried in vacuo to obtain an anthraquinone-based MOF photocatalytic material (brown-yellow powder, denoted as GXMZU106, GXMZU = Guangxi University for Nationalities) with a yield of 65%.
[0038] Comparative Example 1: Preparation of biphenyl MOF photocatalytic material
[0039] (1) Preparation of functional ligands:
[0040]
[0041] 0.5 g of 4,4′-dibromo-1,1′-biphenyl and 1.783 g of 1-THP-4-pyrazoleboronic acid pinacol ester were placed in N,N-dimethylformamide (38 mL) and water (9.5 mL), and 0.8859 g of anhydrous K2CO3 and 0.3704 g of Pd(PPh3)4 were added, and the mixture was heated to 110°C and stirred for 48 hours under a nitrogen atmosphere. After the reaction was completed, the reaction mixture was cooled to room temperature, 50 mL of saturated sodium chloride aqueous solution was added to completely precipitate the solid, and then filtered to obtain a dark gray solid, which was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1, volume ratio) to obtain an intermediate product. The tetrahydropyran protecting group of the intermediate product was deprotected by placing the intermediate product in 50 mL of ethanol, adding 25 mL of hydrochloric acid (1.0 mol / L), heating to 80° C. and stirring for 10 h, cooling at room temperature, filtering, washing the precipitate with ethanol and adding it to a beaker containing 100 mL of distilled water, adjusting the pH to 5.0-7.0 (specifically to pH=7.0 in this example) with sodium hydroxide (aq, 0.5 mol / L), filtering, washing the filter cake with distilled water until neutral, and then rinsing with a small amount of ethanol and ether to obtain a blue-gray solid (referred to as ligand H2pbp) with a yield of 72%.
[0042] (2) Preparation of MOF photocatalytic material: 33 mg of ligand H2pbp was dissolved in 16 mL of N,N-dimethylformamide, and 37.9 mg of Ni(OAc)2·4H2O was dissolved in 4 mL of water. The two solutions were then mixed and heated to 150°C in a reactor for a solvent thermal reaction until completion (about 9 h). After the reaction, the mixture was cooled to room temperature. Solids precipitated, which were collected and washed with solvent N,N-dimethylformamide, ethanol and ether, and dried in vacuo to obtain a biphenyl MOF photocatalytic material (gray powder, denoted as GXMZU104, GXMZU = Guangxi University for Nationalities) with a yield of 70%.
[0043] Comparative Example 2: Preparation of anthracene-based MOF photocatalytic materials
[0044] (1) Preparation of functional ligands:
[0045]
[0046] 0.5 g of 2,6-dibromoanthracene and 1.656 g of 1-THP-4-pyrazoleboronic acid pinacol ester were placed in N,N-dimethylformamide (36 mL) and water (9 mL), and 0.823 g of anhydrous K2CO3 and 0.344 g of Pd(PPh3)4 were added, and the mixture was heated to 110°C and stirred for 48 h under a nitrogen atmosphere. After the reaction was completed, the reaction mixture was cooled to room temperature, 50 mL of saturated sodium chloride aqueous solution was added to completely precipitate the solid, and then filtered to obtain a yellow solid, which was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1, volume ratio) to obtain an intermediate product. The tetrahydropyran protecting group of the intermediate product was deprotected by placing the intermediate product in 50 mL of ethanol, adding 25 mL of hydrochloric acid (1.0 mol / L), heating to 80° C. and stirring for 10 h, cooling at room temperature, filtering, washing the precipitate with ethanol and adding it to a beaker containing 100 mL of distilled water, adjusting the pH to 5.0-7.0 (specifically to pH=7.0 in this example) with sodium hydroxide (aq, 0.5 mol / L), filtering, washing the filter cake with distilled water until neutral, and then rinsing with a small amount of ethanol and ether to obtain a light yellow solid (referred to as ligand DPA) with a yield of 85%.
[0047] (2) Preparation of MOF photocatalytic material: 30 mg of ligand DPA was dissolved in 16 mL of N,N-dimethylformamide, and 31.8 mg of Ni(OAc)2·4H2O was dissolved in 4 mL of water. The two solutions were then mixed and heated to 150°C in a reactor for a solvothermal reaction until completion (about 9 h). After the reaction was completed, the solution was cooled to room temperature and solid precipitated. The solid was collected and washed with solvent N,N-dimethylformamide, ethanol and ether, and dried in vacuo to obtain anthracene-based MOF photocatalytic material (dark brown, denoted as GXMZU105, GXMZU = Guangxi University for Nationalities) with a yield of 57%.
[0048] Comparative Example 3: Preparation of anthraquinone-based MOF photocatalytic materials
[0049] Example 1 was repeated, except that acetonitrile was used instead of N,N-dimethylformamide in step (2).
[0050] After the solvent thermal reaction was completed and cooled to room temperature, no solid was precipitated, so the anthraquinone-based MOF photocatalytic material was not prepared in this example.
[0051] Comparative Example 4: Preparation of anthraquinone-based MOF photocatalytic materials
[0052] Example 1 was repeated, except that Ni(NO3)2·6H2O was used instead of Ni(OAc)2·4H2O in step (2).
[0053] After the solvent thermal reaction was completed and cooled to room temperature, no solid was precipitated, so the anthraquinone-based MOF photocatalytic material was not prepared in this example.
[0054] The ligands and MOF photocatalytic materials prepared in the above Example 1, Comparative Examples 1 and 2 were characterized and analyzed, and the results are as follows:
[0055] 1. Nuclear magnetic resonance hydrogen spectrum and carbon spectrum
[0056] The ligands prepared in Example 1 and Comparative Examples 1-2 were characterized by NMR, wherein:
[0057] Example 1 The H-NMR and C-NMR spectra of the ligand obtained are as follows: Figure 1 As shown. Figure 1 It can be determined that the ligand DPAq prepared in Example 1 is 2,6-bis(pyrazol-4-yl)-9,10-anthraquinone.
[0058] Comparative Example 1 The H NMR and CP spectra of the ligand obtained are as follows: Figure 2 As shown. Figure 2 It can be determined that the ligand H2pbp prepared in Comparative Example 1 is 4,4'-di(1H-pyrazol-4-yl)-1,1'-biphenyl.
[0059] Comparative Example 2 The NMR hydrogen spectrum and carbon spectrum of the ligand obtained are as follows Figure 3 As shown. Figure 3 It can be determined that the ligand DPA prepared in Comparative Example 2 is 2,6-bis(pyrazol-4-yl)-9,10-anthracene.
[0060] 2. Infrared spectroscopy analysis
[0061] The ligands and photocatalytic materials GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1-2 were characterized and analyzed by infrared spectrometer. The characterization results are as follows: Figure 4 As shown. Figure 4 (c) It can be seen that GXMZU106 has a peak at 1670-1678 cm -1 The characteristic peak of the anthraquinone part of the ligand C=O is at 3000-3300 cm -1 The pyrazole peaks on the left and right disappeared, and the infrared image preliminarily indicated the synthesis of the complex (i.e., MOF photocatalytic material).
[0062] 3. PXRD analysis
[0063] The GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1-2 were characterized and analyzed by X-ray powder diffractometer (PXRD). The characterization results are as follows: Figure 5 As shown. Figure 5 It can be seen that the PXRD of GXMZU106 is consistent with its simulated PXRD results. At the same time, the PXRD results of GXMZU104 and GXMZU105 are consistent with that of GXMZU106, indicating that the crystal coordination structures of GXMZU104 and GXMZU105 are the same as those of GXMZU106, and GXMZU106 still maintains high crystallinity and structural integrity even after boiling in 7 mol / L NaOH for 24 h, indicating its chemical stability.
[0064] 4. UV-Vis diffuse reflectance analysis
[0065] Solid UV-visible diffuse reflectance analysis was performed on GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1-2, respectively. The analysis results are as follows: Figure 6 As shown. Figure 6 It can be seen that the absorption edge of GXMZU106 is greater than 700nm, indicating that GXMZU106 has the ability to capture visible light and shows strong electron accepting ability.
[0066] 5. Electrochemical impedance spectroscopy
[0067] Electrochemical impedance spectroscopy (EIS) was performed on GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1-2, respectively. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that GXMZU106 has the smallest impedance, indicating that its charge transfer resistance is lower and more conducive to charge transfer.
[0068] 6. Photocurrent response analysis
[0069] The photocurrent response analysis of GXMZU104, GXMZU105 and GXMZU106 prepared in Example 1 and Comparative Examples 1-2 was performed respectively. The analysis results are as follows: Figure 8 As shown. Figure 8 It can be seen that the photocurrent response generated by GXMZU106 under visible light irradiation is much higher than that of the other two Ni8-MOFs, which shows that the introduction of photoactive electron-withdrawing units into the system is indeed beneficial to the improvement of charge separation efficiency.
[0070] 7.XPS analysis
[0071] X-ray photoelectron spectroscopy (XPS) was used to characterize the GXMZU106 prepared in Example 1 before and after the cycle to determine the composition elements and stability of MOFs. The characterization results are as follows: Fig. 9 As shown. Fig. 9It can be seen that the prepared GXMZU106 samples contain Ni, O, C and N elements, and do not contain other impurity elements, which means that the prepared samples are consistent with the elements obtained from the crystal structure, and the elements are the same before and after the cycle test, which further proves the high stability of the material.
[0072] Example 2: Preparation of anthraquinone-based MOF photocatalytic material crystals
[0073] Ni(OAc)2·4H2O (5 mg, 0.025 mmol), ligand DPAq (6 mg, 0.02 mmol, prepared according to step (1) of Example 1), N,N-dimethylformamide (1.5 mL) and water (0.50 mL) were placed in a 10 mL glass container, and the pH of the system was adjusted to 4.5 with dilute HNO3 (0.25 mol / L); then the glass container was placed in a 120°C environment for reaction for 72 h. After the reaction was completed, it was cooled to room temperature at a rate of 5°C / h, and brown octahedral crystals precipitated. The crystals were collected, which were quinone-based MOF photocatalytic material crystals with a yield of 68%.
[0074] The quinone-based MOF photocatalytic material crystal prepared in this example was characterized and analyzed by X-ray single crystal diffractometer (XRD) to obtain its crystal structure. The crystallographic data are shown in Table 1 below. The crystal structure is shown in Table 1 below. Fig.10 As shown. Fig.10 It can be seen that the eight Ni atoms are bridged by four μ4-OH and two μ4-OH2 oxygens to form [Ni8(μ4-OH)4(μ4-OH2)2(Pz) 12 ] cluster, in which two N atoms of the same pyrazole coordinately cover two adjacent Ni atoms. [Ni8(μ4-OH)4(μ4-OH2)2(Pz) 12 The clusters are further connected with linear bipyrazole to form a three-dimensional porous framework with octahedral and tetrahedral cavities. This structure intuitively represents the synthesis of the complex and its coordination structure.
[0075] The SCXRD (single crystal X-ray diffraction) analysis showed that the obtained crystal had symmetry.
[0076] Table 1 Crystallographic structure data of quinone-based MOF photocatalytic material crystals
[0077]
[0078] a R1=Σ||Fo|-|Fc|| / Σ|Fo|.
[0079] b wR2={Σ[w(Fo 2 -Fc2 ) 2 ] / [w(Fo 2 ) 2 ]}1 / 2,[Fo>4σ(Fo)].
[0080] The quinone-based MOF photocatalytic material crystals prepared in this embodiment were characterized and analyzed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The characterization results are as follows: Fig.11 As shown. Fig.11 It can be seen that the quinone-based MOF photocatalytic material crystals of the present invention are octahedral crystals, and C, O, Ni and N are evenly distributed in the sample.
[0081] Example 3: Preparation of anthraquinone-based MOF photocatalytic materials
[0082] Repeat Example 1, except that:
[0083] In step (1), N,N-dimethylacetamide is used instead of N,N-dimethylformamide.
[0084] In step (2), the reaction temperature was changed to 140°C.
[0085] As a result, a yellow-brown powdery anthraquinone-based MOF photocatalytic material was obtained with a yield of 23%.
[0086] Example 4: Preparation of anthraquinone-based MOF photocatalytic materials
[0087] Repeat Example 1, except that:
[0088] In step (1), 1,4-dioxane is used instead of N,N-dimethylformamide, the amount of tetrakis(triphenylphosphine)palladium is changed to 0.2 times the mass of 1-THP-4-pyrazoleboronic acid pinacol ester, and sodium bicarbonate is used to adjust the pH of the system to 7.0.
[0089] In step (2), the amount of N,N-dimethylformamide was changed to 20 mL and the reaction temperature was changed to 160°C.
[0090] As a result, a brown-yellow powdery anthraquinone-based MOF photocatalytic material was obtained with a yield of 39%.
[0091] Example 5: Preparation of anthraquinone-based MOF photocatalytic material crystals
[0092] Example 2 was repeated, except that the amount of N,N-dimethylformamide was changed to 1.0 mL, the pH of the system was adjusted to 5.5 with dilute sulfuric acid (0.2 mol / L), and the reaction was carried out at 140° C. for 48 h.
[0093] As a result, brown-yellow octahedral crystals were obtained with a yield of 32%.
[0094] The crystals obtained in this example were characterized by an X-ray single crystal diffractometer and confirmed to be the anthraquinone-based MOF photocatalytic material crystals of the present invention.
[0095] Application Example 1
[0096] 5 mg of GXMZU106 prepared in Example 1 and 10.92 μL (0.1 mmol) of benzylamine (C7H9N) were added to a quartz tube, and 4 mL of acetonitrile solution was added. The quartz tube was sealed, and oxygen was bubbled for 20 min. Then, a 500 W, λ>420 nm xenon lamp was used for illumination. The reaction was carried out at room temperature for 6 h. After the reaction was completed, the catalyst was separated and the product was collected. The product yield was measured by gas chromatograph (GC), and the product was determined by nuclear magnetic resonance (NMR) to obtain N-benzyl-1-phenylmethanimine (C7H9N). 14 H 13 N). According to calculation, the yield of N-benzyl-1-phenylformimine is 97% and the selectivity is 100%.
[0097] Material application analysis: After the photocatalytic reaction of GXMZU106 in Application Example 1 was completed, the catalyst GXMZU106 was centrifuged, washed and dried, and then used again to catalyze fresh benzylamine. The experiment was repeated 4 times, and the yields obtained were 97%, 95%, 95%, 94% and 92%, respectively, and the selectivity was 100%. Fig.12 As shown. Fig.12 It can be seen that after 5 cycles of experiments, the effect of GXMZU106 catalyzing the self-coupling of benzylamine has been in a stable state. This cycle experiment shows that the anthraquinone-based MOF photocatalytic material of the present invention has excellent stability, can be reused, and has good economic benefits.
[0098] Application Comparative Example 1
[0099] The only difference between this example and Application Example 1 is that the ligand DPAq prepared in step (1) of Example 1 is used as the catalyst instead of GXMZU106.
[0100] The results showed that the product N-benzyl-1-phenylmethanimine (C 14 H 13 N). According to calculation, the yield of N-benzyl-1-phenylformimine is 92% and the selectivity is 100%.
[0101] Application Comparative Example 2
[0102] The only difference between this example and Application Example 1 is that GXMZU104 prepared in Comparative Example 1 is used as the catalyst instead of GXMZU106.
[0103] The results showed that the product N-benzyl-1-phenylmethanimine (C 14 H13 N). According to calculation, the yield of N-benzyl-1-phenylformimine is 45% and the selectivity is 100%.
[0104] Application Comparative Example 3
[0105] The only difference between this example and Application Example 1 is that GXMZU105 prepared in step (1) of Example 1 is used as the catalyst instead of GXMZU106.
[0106] The results showed that the product N-benzyl-1-phenylmethanimine (C 14 H 13 N). According to calculation, the yield of N-benzyl-1-phenylformimine is 49% and the selectivity is 100%.
[0107] Application Example 2
[0108] The difference between this example and Application Example 1 is that 4-fluorobenzylamine (C7H8FN) is used instead of benzylamine (C7H9N).
[0109] The results showed that the product N-(4-fluorobenzyl)-1-(4-fluorophenyl)methanimine (C 14 H 11 F2N). According to calculation, the yield of N-(4-fluorobenzyl)-1-(4-fluorophenyl)methanimine is 91% and the selectivity is 87%.
[0110] Application Example 3
[0111] The difference between this example and Application Example 1 is only that benzylamine (C7H9N) is replaced by 4-chlorobenzylamine (C7H8ClN).
[0112] The results showed that the product N-(4-chlorobenzyl)-1-(4-chlorophenyl)methanimine (C 14 H 11 C l2 N). According to calculation, the yield of N-(4-chlorobenzyl)-1-(4-chlorophenyl)methanimine is 94% and the selectivity is 100%.
[0113] Application Example 4
[0114] The difference between this example and Application Example 1 is only that 4-bromobenzylamine (C7H8BrN) is used instead of benzylamine (C7H9N).
[0115] The results showed that the product N-(4-bromobenzyl)-1-(4-bromophenyl)methanimine (C 14 H 11 Br2N). According to calculation, the yield of N-(4-bromobenzyl)-1-(4-bromophenyl)methanimine is 93% and the selectivity is 100%.
[0116] Application Example 5
[0117] The difference between this example and Application Example 1 is that 4-trifluoromethylbenzylamine (C8H8FN) is used instead of benzylamine (C7H9N).
[0118] The results showed that the product N-(4-trifluoromethylbenzyl)-1-(4-trifluoromethylphenyl)methanimine (C 16 H 11 F6N). According to calculation, the yield of N-(4-trifluoromethylbenzyl)-1-(4-trifluoromethylphenyl)formanimine is 76% and the selectivity is 100%.
[0119] Application Example 6
[0120] The difference between this example and application example 1 is that 4-methylbenzylamine (C8H 11 N) instead of benzylamine (C7H9N).
[0121] The results showed that the product N-(4-methylbenzyl)-1-(4-methylphenyl)methanimine (C 16 H 17 N). According to calculation, the yield of N-(4-methylbenzyl)-1-(4-methylphenyl)methanimine is 90% and the selectivity is 100%.
[0122] Application Example 7
[0123] The difference between this example and application example 1 is that 4-methoxybenzylamine (C8H 11 ON) instead of benzylamine (C7H9N).
[0124] The results showed that the product N-(4-methoxybenzyl)-1-(4-methoxyphenyl)methanimine (C 16 H 17 O2N). According to calculation, the yield of N-(4-methoxybenzyl)-1-(4-methoxyphenyl)methanimine is 97% and the selectivity is 100%.
[0125] Application Example 8
[0126] The difference between this example and application example 1 is that 2-methoxybenzylamine (C8H 11 ON) instead of benzylamine (C7H9N).
[0127] The results showed that the product N-(2-methoxybenzyl)-1-(2-methoxyphenyl)methanimine (C 16 H 17 O2N). According to calculation, the yield of N-(2-methoxybenzyl)-1-(2-methoxyphenyl)formanimine is 92% and the selectivity is 100%.
[0128] Application Example 9
[0129] The difference between this example and application example 1 is that 3-methoxybenzylamine (C8H 11 ON) instead of benzylamine (C7H9N).
[0130] The results showed that the product N-(3-methoxybenzyl)-1-(3-methoxyphenyl)methanimine (C 16 H 17 O2N). According to calculation, the yield of N-(3-methoxybenzyl)-1-(3-methoxyphenyl)methanimine is 90% and the selectivity is 100%.
[0131] Application Example 10
[0132] The difference between this example and Application Example 1 is that 3-pyridinemethylamine (C6H8N2) is used instead of benzylamine (C7H9N).
[0133] The results showed that the product 1-(pyridin-3-yl)-N-(pyridin-3-methyl)methanimine (C 12 H 11 N3). According to calculation, the yield of 1-(pyridin-3-yl)-N-(pyridin-3-methyl)methanimine is 95% and the selectivity is 100%.
[0134] Application Example 11
[0135] The difference between this example and Application Example 1 is that 2-furylmethylamine (C5H7ON) is used instead of benzylamine (C7H9N).
[0136] The results showed that the product 1-(furan-2-yl)-N-(furan-2-methyl)methanimine (C 10 H9O2N). According to calculation, the yield of 1-(furan-2-yl)-N-(furan-2-methyl)methanimine is 91% and the selectivity is 100%.
[0137] Application Example 12
[0138] The difference between this example and Application Example 1 is that 2-thiophenemethylamine (C5H7SN) is used instead of benzylamine (C7H9N).
[0139] The results showed that the product 1-(thiophene-2-yl)-N-(thiophene-2-methyl)methanimine (C 10 H9S2N). According to calculation, the yield of 1-(thiophene-2-yl)-N-(thiophene-2-methyl)methanimine is 92% and the selectivity is 100%.
Claims
1. An anthraquinone-based MOF photocatalytic material, characterized in that: The invention is obtained by solvothermal reaction of ligand DPAq and nickel source in a mixed solvent; wherein the ligand DPAq is 2,6-bis(pyrazole-4-yl)-9,10-anthraquinone, and the mixed solvent is a composition of N,N-dimethylformamide and water.
2. The anthraquinone-based MOF photocatalytic material according to claim 1, characterized in that: The nickel source is Ni(OAc)2·4H2O.
3. The method for preparing the anthraquinone-based MOF photocatalytic material according to claim 1, characterized in that: The ligand DPAq and the nickel source are dissolved in N,N-dimethylformamide and water respectively, and the two solutions are mixed and then subjected to a solvothermal reaction to obtain the product.
4. The preparation method according to claim 3, characterized in that: The nickel source is Ni(OAc)2·4H2O.
5. The preparation method according to claim 3 or 4, characterized in that: The solvothermal reaction was carried out at ≥100°C.
6. An anthraquinone-based MOF photocatalytic material crystal, characterized in that: This material belongs to the cubic crystal system. Space group, unit cell parameters are: α=90.00°, β=90.00°, γ=90.00°.
7. The method for preparing anthraquinone-based MOF photocatalytic material crystals according to claim 6, characterized in that: The ligand DPAq and the nickel source are placed in a mixed solvent, the pH of the system is adjusted to acidic, and the reaction is carried out under heating conditions. The reaction solution is cooled and crystals are precipitated to obtain the product; wherein the ligand DPAq is 2,6-bis(pyrazol-4-yl)-9,10-anthraquinone, and the mixed solvent is a combination of N,N-dimethylformamide and water.
8. The preparation method according to claim 7, characterized in that: Adjust the pH of the system to 4.0-6.
5.
9. The preparation method according to claim 7, characterized in that: The reaction is carried out at ≥100°C.
10. Use of the anthraquinone-based MOF photocatalytic material according to claim 1 or the anthraquinone-based MOF photocatalytic material crystal according to claim 6 in photocatalytic benzylamine self-coupling reaction to prepare imine compounds.
Citation Information
Patent Citations
Photosensitive MOF catalyst and preparation method and application thereof
CN116371471A
Conjugated porous polymer, preparation method thereof, and application thereof in imine preparation through photo-catalyzed oxidation of primary amine
CN110452365A
Anthraquinone-based two-dimensional MOF photocatalyst as well as preparation method and application thereof
CN117700766A
Cited By
Transition metal-based high-specific-surface-area metal organic framework material, preparation method thereof and application of transition metal-based high-specific-surface-area metal organic framework material in methane storage
CN121930494A
A transition metal-based high specific surface area metal organic framework material, a preparation method thereof and application thereof in methane storage
CN121930494B